ANALYSIS OF FACTORS RELATED TO SELF CARE MANAGEMENT IN HEART FAILURE PATIENTS : SCOPING REVIEW - Siregar, Latifah (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
Heart failure affects 23 million people throughout the world. In Indonesia, heart failure always increases every year, the prevalence of heart failure in the last six years was 1.67% from 2013 to 2018. Self-care for heart failure patients is very necessary for success management and control of these chronic diseases. The aim of this scoping review is to identify factors associated with self-care in patients with heart failure. This article review uses the Scoping Review approach, in this study the researcher used the PEO format in the literature search. The online databases used were Science Direct, PubMed and Scopus. There are 12 articles that are considered to meet the requirements and criteria. After scoping, there were 7 major themes regarding factors that influence self-care management in heart failure patients, namely low knowledge, psychological problems, motivational expectations, communication information, social, spiritual and economic support. Patients with heart failure are likely to experience depression which makes the patient unable to care for themselves, so patients must be given knowledge, information from the medical team, important information for heart failure patients is self-care, this requires hope from the patient, strong spiritual , economic, and family support which are the keys to recovery in patients with heart failure.